The Role of the IBSA Fund in Foreign Aid Policies of IBSA and BRICS Member States - V. A. Dmitrieva; D. A. Kuznetsov (Vestnik MGIMO-Universiteta)
The IBSA Fund, which marks its 20th anniversary in 2024, has extended SouthSouth cooperation to 34 states since its establishment in 2004. This article aims to compare the recipients of bilateral development assistance from IBSA members with IBSA Fund projects’ partners. The objective is to discern the motivations behind the selection of the Fund’s project partners, assess the influence of member states on partner selection, and explore the potential benefits of including Russia and China (both BRICS and New Development Bank participants) as members. The authors analyze the structure, mechanisms, and priorities of IBSA projects, juxtaposing them with New Development Bank projects to highlight key differences and assess shortcomings. The research draws on releases and reports from development agencies, AidData databases, and online databases detailing cooperation projects of all IBSA members and the IBSA Fund. The analysis reveals that the IBSA Fund serves as an additional tool for member states in development cooperation, driven by shared opportunities and responsibilities. Partner selection appears largely motivated by the national interests of IBSA states. While both the IBSA Fund and New Development Bank espouse similar development principles, goals, and narratives, they exhibit differences in terms of development cooperation modalities, emphasis on loans versus grants, project geography, and priorities. As this makes closer cooperation between the two entities unreasonable, Russia and China, whose development assistance priorities largely align with those of the IBSA members, could still be included in the IBSA Fund mechanism, particularly if additional funding is required.